Potential relevance of shear stress for slit diaphragm and podocyte function - Kriz, Wilhelm; Lemley, Kevin V. (Kidney international, 2017)
Filtrate flow through the glomerular barrier produces shear stresses that tend to disconnect podocytes from the glomerular basement membrane. Forces are highest within the filtration slits. The slit diaphragm mechanically balances the lateral components of the shear stresses on opposing foot processes, preventing widening of the slit.